Consumer awareness and satisfaction towards organic products in Palakkad district-Kerala - Abisha KA and P Kannan (Interna tional Jo urna l o f Applied Research, 2018)
The adoption of organic production and processing is highly determined by market demand. Therefore this is reflected in consumer’s awareness and satisfaction towards organic food products. This research result indicated that the main reason for purchasing organic food products is an expectation of a healthier and environment friendly means of production. Organic buyer tend to be older and higher educated than who do not buy them. However, the main barrier to increase the market share of organic food product is consumer information.